Growing debt burden in low- and middle-income countries during COVID-19 may constrain health financing - Frederik Federspiel; Josephine Borghi; Melisa Martinez-Alvarez (Taylor & Francis Group, 2022)
Debt burdens are growing steadily in Low- and Middle-Income Countries (LMICs), compounded by the COVID-19 economic recession, threatening to crowd out essential health spending. In 2019, 54 LMICs spent more on servicing their debt to foreign creditors than on financing their health services. While development loans may have positive effects on population health, the ensuing debt servicing requirements may have detrimental effects on health through constrained fiscal space for government health spending. However, the existing evidence is inadequate for an understanding of whether, and if so how and under what circumstances, debt may constrain government health spending. We call for more research on the impacts of debt on health financing and call on creditors and borrowers to carefully consider the potential impacts of lending on borrower countries' ability to finance their health services.